A Cre-driver rat model for anatomical and functional analysis of glucagon (Gcg)-expressing cells in the brain and periphery - Huiyuan Zheng; Lorena López-Ferreras; Jean-Phillipe Krieger; Stephen Fasul; Valentina Cea Salazar; Natalia Valderrama Pena; Karolina P. Skibicka; Linda Rinaman (Elsevier, 2022)
Objective: The glucagon gene (Gcg) encodes preproglucagon, which is cleaved to form glucagon-like peptide 1 (GLP1) and other mature signaling molecules implicated in metabolic functions. To date there are no transgenic rat models available for precise manipulation of GLP1-expressing cells in the brain and periphery. Methods: To visualize and manipulate Gcg-expressing cells in rats, CRISPR/Cas9 was used to express iCre under control of the Gcg promoter. Gcg-Cre rats were bred with tdTomato reporter rats to tag Gcg-expressing cells. Cre-dependent AAVs and RNAscope in situ hybridization were used to evaluate the specificity of iCre expression by GLP1 neurons in the caudal nucleus of the solitary tract (cNTS) and intermediate reticular nucleus (IRt), and by intestinal and pancreatic secretory cells. Food intake was assessed in heterozygous (Het) Gcg-Cre rats after chemogenetic stimulation of cNTS GLP1 neurons expressing an excitatory DREADD. Results: While genotype has minimal effect on body weight or composition in chow-fed Gcg-Cre rats, homozygous (Homo) rats have lower plasma glucose levels. In neonatal and adult Gcg-Cre/tdTom rats, reporter-labeled cells are present in the cNTS and IRt, and in additional brain regions (e.g., basolateral amygdala, piriform cortex) that lack detectable Gcg mRNA in adults but display transient developmental or persistently low Gcg expression. Compared to wildtype (WT) rats, hindbrain Gcg mRNA and GLP1 protein in brain and plasma are markedly reduced in Homo Gcg-Cre rats. Chemogenetic stimulation of cNTS GLP1 neurons reduced overnight chow intake in males but not females, the effect in males was blocked by antagonism of central GLP1 receptors, and hypophagia was enhanced when combined with a subthreshold dose of cholecystokinin-8 to stimulate gastrointestinal vagal afferents. Conclusions: Gcg-Cre rats are a novel and valuable experimental tool for analyzing the development, anatomy, and function of Gcg-expressing cells in the brain and periphery. In addition, Homo Gcg-Cre rats are a unique model for assessing the role of Gcg-encoded proteins in glucose homeostasis and energy metabolism.